The Moneda Bug, Chrysodarecus moneta Breddin = Placocoris viridis Mayr (Pentatomidae: Discocephalinae: Ochlerini) - Thomas, Donald B. (Zootaxa, 2021)
The pentatomid genus Placocoris Mayr is removed from Pentatominae and placed in Discocephalinae: Ochlerini based on the trichobothrial arrangement. Within the Ochlerini Placocoris shares characteristics with a clade composed of Adoxoplatys and allies including the rostrum arising anteriorad, abdomen with tubercle at middle base received by a notch in the metasternum, bucculae confluent posteriorly, pronotum flat, and a double row of spines on the femora. It appears to share the same host plants with Neoadoxoplatys, species of bamboo. It is further concluded that the genus Chrysodarecus Breddin is a junior synonym of Placocoris Mayr.